Pengaruh Manajemen Talenta dan Manajemen Pengetahuan terhadap Kinerja Pegawai Dinas Pekerjaan Umum dan Tata Ruang (PUTR) Toraja Utara - Diayanti Marse Patung; Adriana Madya Marampa; Olivia Devi Yulian Pompeng (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study was to determine whether there is an influence of talent management and knowledge management on the performance of employees of the North Toraja Public Works and Spatial Planning Agency. The data collection procedures for this study are observation, questionnaires and documentation. The method used in this study is the Quantitative Method using Multiple Linear Regression and processed using SPSS version 26. This study was conducted on employees of the North Toraja Public Works and Spatial Planning Agency with a sample of 50 respondents. The sampling technique used was a saturated sample, namely the population is the same as the sample. The results of the study show that talent management (X1) influences Employee Performance (Y) of North Toraja PUTR with a significance value of 0.035 <0.05. Knowledge management (X2) influences Employee Performance (Y) of North Toraja PUTR with a significance value of 0.000 <0.05. Talent Management (X1) and Knowledge Management (X2) simultaneously influence Employee Performance (Y) with a significance value of 0.000 < 0.05 and an F-value of 78.758 > F-table 3.20.